Is Cultural-Historical Activity Theory Threatened to Fall Short of its Own Principles and Possibilities as a Dialectical Social Science? - Langemeyer, Ines; Roth, Wolf-Michael (Outlines. Critical Practice Studies, 2006)
In recent years, many researchers engaged in diverse areas and approaches of “cultural-historical activity theory” (CHAT) realized an increasing international interest in Lev S. Vygotsky’s, A. N. Leont’ev’s, and A. Luria’s work and its continuations. Not so long ago, Yrjö Engeström noted that the activity approach was still “the best-held secret of academia” (p. 64) and highlighted the “impressive dimension of theorizing behind” it. Certainly, this remark reflects a time when CHAT was off the beaten tracks. But if this situation begins to change today, in which direction will CHAT be heading? Will it continue to be one of those projects “unique for its practical, political, and civic engagement” committed “to ideals of social justice, equality, and social change” as it was in the beginning (Stetsenko & Arievitch, 2004, p. 58)? Although a positive future of CHAT seems to lie ahead, we consider in this article some of the problematics that may challenge all those who want to pass the “impressive dimensions of theorizing” from “insider” circles to a larger audience and from one generation to another as well as encourage newcomers to become part of this tradition through critical engagement in its theory and practice. A key to these engagements, we suggest, is not only the comprehensive empirical and philosophical basis, but also the role of dialectics as both topic and method. Therefore, the challenge for newcomers (as well as for “old-timers”) to take on the tradition of CHAT is not a small one indeed. We assume that a major reason for the increasing interest in CHAT lies in its potential to provide a non-reductionist approach to human development, which is due to its affinity to dialectics; however, the close interrelation to a tradition that reaches back to the theories of Georg W.F. Hegel and Karl Marx, among others, is not the easiest to master. In consideration of these difficulties, the purpose of this article is to investigate how contemporary approaches within CHAT can continue to provide a dialectical framework to preserve and renew the critical intention of this tradition, and how we run the risk of losing this sting. Thereby, we sensitize researchers to the problem of developing a cultural-historical approach within a historical situation that confronts us with new, unanswered questions. In this light, we also problematize the use of scientific language, for it may lead us to speak and argue un-dialectically when in fact we intend or ought to think dialectically. This article seeks to convey insights and arguments of how we can relate our theoretical approaches to a tradition of dialectical thinking and in what ways this is paramount for a critical engagement in theory and practice. In the first part, we therefore discuss not only some major theorems in Hegel’s and Marx’s work but also, and above all, Vygotsky’s way of developing the cultural-historical approach of psychology. Second, we argue that the contemporary, widely known version of CHAT, related to Yrjö Engeström’s theoretical and empirical work, neglects different aspects of dialectical thinking and consequently narrows its potential to a socio-critical approach to societal practice and human development. A crucial question of this scrutiny will be the notion of contradictions and how development is supposed to be achieved. In general, our intention is not only to clarify the role of dialectics as a method for activity theory but also to problematize the role of the subjects of research in CHAT and to confront ourselves with the problems of practicing and developing a critical science in face of a complex and challenging societal world.